Quantification of the ionization probability during desorption/ionization of oligopeptides induced by neutral cluster impact. (14th April 2013) - Lee, B.‐J.; Baur, M.; Gebhardt, C. R.; Dürr, M.
<x xml:space="preserve">Abstract</x> RATIONALE Desorption‐and‐ionization induced by neutral cluster impact is a soft and matrix‐free method, which leads to the formation of free ions of oligopeptides and smaller proteins without fragmentation. As a prerequisite for its successful application in bioanalytics, especially with respect to sensitivity, the ionization efficiency, i.e., the ion‐to‐neutral ratio of the desorbing molecules, was determined. METHODS Neutral SO2 clusters of 103 to 104 molecules in size were seeded in a pulsed He beam and used to desorb and ionize oligopeptides by means of cluster surface impact. The samples were prepared by drop casting a well‐defined amount of substance on the substrate surface; the desorbing ions were identified by means of time‐of‐flight mass spectrometry. Furthermore, the ion current leaving the surface was determined for positive ions, which predominate in the investigated oligopeptides. RESULTS For angiotensin II, bradykinin (1‐7), and adrenocorticotropic hormone (34‐39), the number of ions desorbed from the respective samples was compared with the amount of substance applied on the substrate. Assuming that all biomolecules were desorbed during the experiment, the ion‐to‐neutral ratio or ionization efficiency η was determined. For the tested molecules, values of η between 0.5% and 3% were observed; the substrate material and the total amount of substance applied were shown to have a minor effect on the results. CONCLUSIONS The ion‐to‐neutral ratio in desorption/ionization of oligopeptides induced by neutral cluster impact was determined to be of the order of 10−3 to 10−2. The soft and matrix‐free nature of the method in combination with this value of η might be interesting for applications in bioanalytics. Copyright © 2013 John Wiley & Sons, Ltd.